Sociological Features Of Urdu And English Memes: An Analysis (Journal of Namibian Studies : History Politics Culture, 2023)
In the contemporary realm of digitized existence, memes have become the norm of our virtual culture, omnipresent across the various platforms of social media. Functioning as a distinct and advanced mode of communication, memes enable social media users with an unfettered avenue to communicate their thoughts, jokes, ideas, critiques, etc. This study focuses on English and Urdu memes as one of the internet communication phenomena and their specific sociological features that make these memes interesting sociologically. Here mainly the memes that are in the form of images with a piece of written text on them are considered. Within the purview of this exploration, the General Theory of Verbal Humor presented by Raskin and Salvatore in 1991,  has been undertaken as an analytical lens. Six memes apiece from both English and Urdu have been selected for the analysis. From the results, it was shown that memes are used as strong social expressions. These reflect public reactions to political, social, and economic events, depicting the strong influence of technology on social behaviors. Urdu memes, being intrinsically rooted in the national fabric of Pakistan, emerges as more understandable and relatable to a Pakistani layman. In this way, Urdu memes stand distinguished for their contextual alignment with the Pakistani society, when put against English memes.